Do Digital Competitiveness and Government Efficiency Affect Macroeconomic? An Evidence From Asia-Pacific Countries - Ernawati Ernawati; Muhammad Natsir; Mansyur Asri (ETIKONOMI, 2024)
Research Originality: This research divided the dimensions of digital competitiveness into knowledge, digital policy, and IT integration. The digital competitiveness variable was estimated simultaneously with government efficiency in influencing macroeconomic performance in Asia Pacific countries. This research proved the important role of responsive digital policies and government efficiency in driving the macroeconomy.Research Objectives: This research aimed to determine the effect of digital competitiveness and government efficiency on macroeconomic performance.Research Methods: Data was sourced from the International Institute for Management Development (IMD) publication from 2019 to 2022 for 13 Asia Pacific countries. The digital competitiveness considered in this research is knowledge, digital policy, and IT integration variables. Data was analyzed and processed using panel data regression.Empirical Results: The result showed that digital policy variables reduced macroeconomic performance, while government efficiency positively affected macroeconomic performance. Furthermore, the digital knowledge and IT integration variables did not significantly affect macroeconomic performance.Implications:  This research has significant implications for the development of responsive digital policies that promote macroeconomic performance. It also underscores the importance of governance by the government in controlling the high-cost economy to encourage productivity and macroeconomic performance. These implications provide valuable insights for policymakers and professionals in the field of economics and digital policy.JEL Classification: E60, H11, O39How to Cite:Ernawati, E., Natsir, M., & Asri, M. (2024). Do Digital Competitiveness and Government Efficiency Affect Macroeconomy? An Evidence from Asia Pacific Countries. Etikonomi, 23(2), 481-496. htttps://doi.org/10.15408/etk.v23i2.34339.